Results in Projective Geometry PG(r,23) , r 1,2 - Al-Zangana , Emad Bakr (Iraqi Journal of Science, 2022)
In projective plane over a finite field q F , a conic is the unique complete(q 1) arc and any arcs on a conic are incomplete arc of degree less than q 1.These arcs correspond to sets in the projective line over the same field. In this paper,The number of inequivalent incomplete k  arcs; k  5,6, ,12, on the conic inPG(2,23) and stabilizer group types are found. Also, the projective linePG(1,23) has been splitting into two 12-sets and partitioned into six disjointtetrads.